Sending Carbon Monoxide (CO) Concentration Data to MS Excel and Creating a Database (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
There are several ways to detect and monitor work gas, and it is now advisable to select the most appropriate one. This article describes solutions for sending information from the MQ-7 sensor to the MS Excel program directly for a certain period of time and storing it in the form of a database.